Approximation Theory XIV: San Antonio 2013 - Fasshauer, Gregory E.; Schumaker, Larry L. (Springer Proceedings in Mathematics & Statistics,, 2014)
This volume developed from papers presented at the international conference Approximation Theory XIV,  held April 7-10, 2013 in San Antonio, Texas. The proceedings contains surveys by invited speakers, covering topics such as splines on non-tensor-product meshes, Wachspress and mean value coordinates, curvelets and shearlets, barycentric interpolation, and polynomial approximation on spheres and balls. Other contributed papers address a variety of current topics in approximation theory, including eigenvalue sequences of positive integral operators, image registration, and support vector machines. This book will be of interest to mathematicians, engineers, and computer scientists working in approximation theory, computer-aided geometric design, numerical analysis, and related approximation areas.